A comparison study between previous and current shoreline concentrations of heavy metals at the Great Salt Lake using portable X-ray fluorescence analysis. Issue 8 (17th November 2017) - Thorsen, Marie L.; Handy, Rod G.; Sleeth, Darrah K.; Thiese, Matthew S.; Riches, Naomi O.
ABSTRACT: The Great Salt Lake has been gradually desiccating, increasing the amount of exposed lakebed and potentially exposing heavy metals that may be present in the lakebed soil and sediments. It is hypothesized that there is a statistically significant difference between the current and previous shorelines, with the highest concentrations being at the current shoreline. This study used systematic sampling to collect 32 samples from the current shoreline and previous shorelines (elevation of 1281 and 1282 m, respectively) for a total of 64 samples. All samples underwent X-ray fluorescence analysis to quantify heavy metal concentrations. Nearly all samples contained arsenic (highest concentrations near the current shoreline). The majority of samples (80%) showed mercury levels below the limit of detection (LOD). A statistically significant difference in heavy metal concentrations between the two locations for arsenic, zinc, iron, manganese, rubidium, zirconium, and strontium was found. In addition, it was determined that the relationship between sample size (the number of values above the LOD) and location was statistically significant for mercury, selenium, lead, nickel, copper, manganese, zirconium, and thorium. Further research quantifying heavy metal concentrations in other parts of the Great Salt Lake and the potential for airborne exposures should be conducted.